2021
DOI: 10.1111/josh.13010
|View full text |Cite
|
Sign up to set email alerts
|

National Survey of School Employees: COVID‐19, School Reopening, and Student Wellness

Abstract: BACKGROUND During spring 2020, COVID‐19 forced widespread United States school building closures in an unprecedented disruption for K‐12 students and staff. Partnering with the American School Health Association (ASHA), we sought to identify areas of concern among school staff planning for school reopening with the goal of addressing gaps in resources and education. METHODS This 16‐item web‐based survey was distributed via email to 7467 ASHA members from May to June 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 12 publications
2
31
1
1
Order By: Relevance
“…Past research has found such differences in access and use based on gender (Elena-Bucea et al, 2020), race/ethnic (Yoon et al, 2020), and socio-economic status (SES; Harris et al, 2017) affect K-12 students' educational opportunities even under "normal" prepandemic circumstances (Dolan, 2015). Aside from the access to online educational resources for learning, school closures themselves may have cut students off from other critical resources necessary to support their mental and physical health and overall well-being (Martin & Sorensen, 2020;Pattison et al, 2021). These factors combined contributed to the "twin pandemic" in the United States, such that minoritized individuals, particularly those based on race/ethnicity and socioeconomic status, experienced greater hardship during the pandemic due to inequalities related to differences in structural and societal factors as access to health resources (Chen et al, 2021).…”
Section: Learningmentioning
confidence: 99%
“…Past research has found such differences in access and use based on gender (Elena-Bucea et al, 2020), race/ethnic (Yoon et al, 2020), and socio-economic status (SES; Harris et al, 2017) affect K-12 students' educational opportunities even under "normal" prepandemic circumstances (Dolan, 2015). Aside from the access to online educational resources for learning, school closures themselves may have cut students off from other critical resources necessary to support their mental and physical health and overall well-being (Martin & Sorensen, 2020;Pattison et al, 2021). These factors combined contributed to the "twin pandemic" in the United States, such that minoritized individuals, particularly those based on race/ethnicity and socioeconomic status, experienced greater hardship during the pandemic due to inequalities related to differences in structural and societal factors as access to health resources (Chen et al, 2021).…”
Section: Learningmentioning
confidence: 99%
“…The COVID‐19 pandemic has led to disruptions across all aspects of life, particularly in schools. To date, 3 surveys have provided some insight into the delivery of school‐based health services during the pandemic 5‐7 . These surveys were primarily focused on reopening and pandemic‐related health and safety concerns in schools, as they were conducted during the spring and summer of 2020, when guidance on school reopening was evolving 8 .…”
mentioning
confidence: 99%
“…In particular, the acknowledgement that meeting students’ mental and emotional health needs was a key purpose of the network of support was striking. These findings are supported by a nationwide survey of school employees reporting that WSCC components, including the mental health of students, were a concern among the majority of respondents [ 44 ]. As was further brought to light by the events of 2020, trauma-informed practices, including recognizing the role inequities among racial/ethnic minorities and socioeconomically disadvantaged children play in perpetuating health and educational disparities, warrant serious and sustained attention in school communities [ 45 ].…”
Section: Discussionmentioning
confidence: 56%